Prerequisites Involving Information and Educational Activities to Promote a Healthy Lifestyle for Muscovites: Sociological Analysis - Chizh, N. V. (City Healthcare, 2024)
Introduction. In the context of urbanization, it seems appropriate to improve the infrastructure for information and educational initiatives aimed at promoting a healthy lifestyle among city residents. To implement city policies focused on health preservation, it is necessary to study the prerequisites that contribute to the formation of a healthy lifestyle. The purpose of the study was to identify the prerequisites for improving the infrastructure of information and educational activities to promote a healthy lifestyle for Moscow residents. Materials and methods. The research employed a comprehensive design that integrated quantitative and qualitative research methods. The analysis included: 1) media analysis of social media content from 2019 to 2024; 2) the results of the “Moscow is a healthy city” survey conducted by VCIOM in 2018; 3) a pilot questionnaire survey of Muscovites conducted by the author of the article (762 respondents); 4) interview materials collected by the author of the article (6 experts knowledgeable about health preservation in Moscow). Results. The study showed an increase in the number and diversity of the relevant subjects. It was revealed that the topic of health preservation is covered not only in specialized media but also in mainstream news or those focusing on other topics that are not directly related to health. However, media content presents both a positive description of events related to the health of Moscow residents and a negative one, reflecting the causes of health deterioration. It was revealed that Muscovites receive the necessary information about health preservation only when they have already become patients of Moscow clinics or clients of social services. Conclusion. Moving forward, Moscow authorities should pay closer attention to targeted preventive educational work with citizens before they face severe health problems and seek help from medical and social organizations.